IMPLEMENTATION OF LESSON STUDY IN MICROTEACHING: BENEFITS AND CHALLENGES IN ENGLISH EDUCATION STUDY PROGRAM - Endang Darsih; Vina Agustiana; Wulan Rahmatunisa (Indonesian Journal of Learning and Instruction, 2023)
This study investigates the implementation of Lesson Study in microteaching classes within the English Education program, focusing on its impact and perceived challenges among students. Utilizing a mixed methods approach, data was collected through observations and surveys from 10 participants enrolled in the microteaching course. Findings reveal that Lesson Study effectively enhances teaching skills through collaborative planning and reflective sessions, fostering deeper insights into effective teaching strategies. However, challenges such as time constraints, logistical complexities in scheduling, and the integration of technology were identified as significant hurdles. Addressing these challenges is crucial for optimizing the benefits of Lesson Study in enhancing teaching practices and facilitating professional growth among future educators.